PELAKSANAAN HAK ATAS KESEHATAN BAGI PEGAWAI NEGERI SIPIL SEBAGAI BAGIAN DARI HAK ASASI MANUSIA PADA PT. ASKES (PERSERO) PEKANBARU - Deliana, Evi (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2010)
Human rights are inherent rights for human being. It is independent from the influence of the law system and government.Â One of those rights is the right of health. PT. Askes (Persero) is one of the companies which hold health insurance for civil servants (Pegawai Negeri Sipil/PNS). Based on legislation, civil servants must join this insurance. The problem is civil servants do not have information about their right and duty in health insurance contract. However, health institutions do not give their service well for civil servants.Keywords: human rights, health insurance, civil servants.